Karakteristik Organoleptik Permen Jelly Gelatin Tulang Ikan Gabus (Ophioceplaus striatus) dengan Penambahan Lendir Okra - Fitra Mulia Jaya; Rih Laksmi Utpalasari; Rendi Kurniawan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Fitra MJ, Utpalasari RL, Kurniawan R. 2020. Organoleptic characteristics of jelly candy from catfish bone gelatin (Ophioceplaus striatus) with the addition of okra slime. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The availability of raw material for gelatin from waste, especially fish bones in Palembang city is high enough. Therefore, gelatin that is processed from raw fish waste can be used as an alternative of halal gelatin besides gelatin derived from beef bones. Gelatin is widely used in industries, especially the food processing industry such as jelly candy. Candies are sweets, it was made by mixing a certain concentration of sugar into water and then adding flavor. Many people deliberately eat candy while doing various activities. Candy is considered as a snack that can help the mind become fresher so that it will certainly make us concentrate or thinking better. The high sugar content in candy products can often lead to problems caused by excessive sugar consumption. In this study, the researchers added okra mucus, which apart from being rich in vitamins and minerals, okra is also rich in fiber. However, the use of okra slime into food products, especially candy, is still limited because people don't like the mucus found in okra fruit. Futher more, researchers added okra slime to candy made from fish gelatin so that it could be accepted by the public. This research was conducted at the UPGRI Palembang THP Workshop and agricultural products laboratory, Faculty of Agriculture, Sriwijaya University. This study aimed to determine the level of preference for the panelists to jelly candy added with okra fruit mucus which includes PO1 was 0%, PO2 was 2.5%, PO3 was 5%, PO4 was 7.5% and 10%. The results of the organolpetic analysis data were analyzed by using the non-parametric Friedman Conover statistical test. The results showed that the addition of okra slime to jelly candy made of Gabus fish waste gelatin (Ophiocepalus striatus) had a significant effect on appearance, aroma and taste. The best treatment was the PO2 treatment (jelly candy from snakeheadfish waste gelatin with the addition 2.5% of okra slime) with a liking level of appearance was 3.50 (good), aroma was 3.03 (rather good) and taste was 3.73 (good ).Keywords : Gelatin, Okra Slime, Jelly Candy